Pedunculopontine arousal system physiology—Implications for schizophrenia - Garcia-Rill, Edgar (Sleep Sci, 2015)
Schizophrenia is characterized by major sleep/wake disturbances including increased vigilance and arousal, decreased slow wave sleep, and increased REM sleep drive. Other arousal-related symptoms include sensory gating deficits as exemplified by decreased habituation of the blink reflex. There is also dysregulation of gamma band activity, suggestive of disturbances in a host of arousal-related mechanisms. This review examines the role of the reticular activating system, especially the pedunculopontine nucleus, in the symptoms of the disease. Recent discoveries on the physiology of the pedunculopontine nucleus help explain many of these disorders of arousal in, and point to novel therapeutic avenues for, schizophrenia.